1995
DOI: 10.1128/jcm.33.2.419-427.1995
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot interpretation criteria for serodiagnosis of early Lyme disease

Abstract: We monitored the antibody responses of 55 treated patients with early Lyme disease and physiciandocumented erythema migrans. Six sequential serum samples were obtained from patients before, during, and until one year after antibiotic therapy and analyzed by in-house enzyme-linked immunosorbent (ELISA) and immunoblot assays. An immunoblot procedure utilizing a gradient gel and an image analysis system was developed. A relational database management system was used to analyze the results and provide criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
150
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(166 citation statements)
references
References 33 publications
10
150
1
5
Order By: Relevance
“…The specificity of 2-tiered testing has generally been у95%, both in our unpublished studies and as reported by reference laboratories, including our own [13,14,42,43]. In the general practice of 2-tiered testing, standardization of the performance, scoring, and interpretation of immunoblots is sometimes difficult, and the quality of results provided to physicians may be lower than the best achievable [7,42,43]. Furthermore, our study used a single commercial ELISA and immunoblots from a single manufacturer for 2tiered testing; results with other products may vary.…”
Section: Discussionsupporting
confidence: 65%
“…The specificity of 2-tiered testing has generally been у95%, both in our unpublished studies and as reported by reference laboratories, including our own [13,14,42,43]. In the general practice of 2-tiered testing, standardization of the performance, scoring, and interpretation of immunoblots is sometimes difficult, and the quality of results provided to physicians may be lower than the best achievable [7,42,43]. Furthermore, our study used a single commercial ELISA and immunoblots from a single manufacturer for 2tiered testing; results with other products may vary.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, like OspA and OspB, lp6.6 did not generate an antibody response in mice or rhesus monkeys following low-dose needle or tick inoculation, respectively, despite the fact that the native molecule is extremely immunogenic when administered in the context of killed borreliae. These findings appear to be relevant to human Lyme borreliosis in that antibodies directed against low-molecular-mass B. burgdorferi antigens typically are absent, particularly during early human infection (8,24,27,28,59). All of these findings lead us to postulate that, analogous to that of the OspA and OspB genes (25,54), the expression of lp6.6 occurs in the tick vector but is downregulated during mammalian infection.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, DNA sequence analysis allowed us to determine that the molecular mass of the 51-amino-acid mature, acylated polypeptide is about 6.6 kDa. Other studies have noted the existence in B. burgdorferi of low-molecular-mass polypeptides and lipoproteins (28,52,62), but their relationship to lp6.6 remains uncertain. As a cautionary note, investigators should be aware of the need to shorten resolution times during SDS-PAGE in order to visualize lp6.6 or other low-molecular-mass borrelial polypeptide constituents.…”
Section: Discussionmentioning
confidence: 98%
“…Typically, laboratory testing of LD follows identification of cutaneous manifestations from visual inspection but these manifestations are not always present. Current guidelines recommend serologic testing, a twophase process consisting of an enzyme immunoassay within 30 days of symptom onset, followed by Western blot after 30 days from symptom occurs 7,8 if the early test is active. Even together, this diagnostic strategy has poor sensitivity, particularly during the acute phase, with false-negative rates of up to 50% 9 .…”
Section: Introductionmentioning
confidence: 99%